2001
DOI: 10.1016/s1097-2765(01)00318-5
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Calnexin, an ER Chaperone Involved in Quality Control of Protein Folding

Abstract: The three-dimensional structure of the lumenal domain of the lectin-like chaperone calnexin determined to 2.9 A resolution reveals an extended 140 A arm inserted into a beta sandwich structure characteristic of legume lectins. The arm is composed of tandem repeats of two proline-rich sequence motifs which interact with one another in a head-to-tail fashion. Identification of the ligand binding site establishes calnexin as a monovalent lectin, providing insight into the mechanism by which the calnexin family of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
327
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(337 citation statements)
references
References 53 publications
(2 reference statements)
8
327
0
2
Order By: Relevance
“…Because Trichomonas has a predicted N-glycan precursor (Man 5 GlcNAc 2 ) that lacks Glc (Table 1 and (Fig. 4A) (2, 7).…”
Section: N-glycan-dependent Qc Of Glycoprotein Folding Is Functional Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Trichomonas has a predicted N-glycan precursor (Man 5 GlcNAc 2 ) that lacks Glc (Table 1 and (Fig. 4A) (2, 7).…”
Section: N-glycan-dependent Qc Of Glycoprotein Folding Is Functional Inmentioning
confidence: 99%
“…Fifth and finally, the Saccharomyces UGGT ortholog (Kre5) is deeply divergent (SI Fig. 9), so that it no longer glucosylates In the absence of UDP-Glc the predominant product was NYT-hex 5, whereas in the presence of UDP-Glc the predominant products were NYT-hex 5 and NYT-hex6. (B) HPLC analysis of enzymatic digestion of the latter products showed NYT-hex 5 was Man 5GlcNAc2 and NYT-hex6 was GlcMan5GlcNAc2.…”
Section: Argument For the Secondary Loss Of N-glycan-dependent Qc Ofmentioning
confidence: 99%
“…For the chaperone probe, we selected Crt for several reasons: the availability of a knockout cell line (19), chemical inhibitors of its function (20), well characterized biochemical properties (21)(22)(23)(24)(25)(26), and structural information (24,(27)(28)(29). Based on this information, we generated a GFP-tagged Crt (Crt-GFP) (Fig.…”
mentioning
confidence: 99%
“…From the recently solved three-dimensional structures of the CRT P-domain and the luminal domain of CNX (24,25), it was revealed that both chaperones contain a globular lectin domain with a long, protruding arm-like extension, referred to as the P-domain. The site of interaction with ERp57 has been mapped to the outermost tip of the P-domain in both CNX and CRT (26 -28).…”
mentioning
confidence: 99%